2017
DOI: 10.1051/0004-6361/201731378
|View full text |Cite
|
Sign up to set email alerts
|

Density diagnostics of ionized outflows in active galactic nuclei

Abstract: Context. Ionized outflows in active galactic nuclei (AGNs) are thought to influence their nuclear and local galactic environment. However, the distance of the outflows with respect to the central engine is poorly constrained, which limits our understanding of their kinetic power as a cosmic feedback channel. Therefore, the impact of AGN outflows on their host galaxies is uncertain. However, when the density of the outflows is known, their distance can be immediately obtained from their modeled ionization param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 39 publications
2
58
0
Order By: Relevance
“…The absorption features caused by the warm absorber are accounted for using six PION components. In both the 2013-2014 and 2016 spectra, the hydrogen column densities (N H ), outflow velocities (v out ), and microscopic turbulence velocities (v mic ) of the PION components are fixed to values given in Mao et al (2017), which are obtained by fitting the high quality 2002 Chandra grating spectra of NGC 5548. Nonetheless, the ionization parameters (log ξ) can differ for these three epochs, due to the variability of the obscurer, as well as the changes of the intrinsic SED (Cappi et al 2016).…”
Section: The Physical Global Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption features caused by the warm absorber are accounted for using six PION components. In both the 2013-2014 and 2016 spectra, the hydrogen column densities (N H ), outflow velocities (v out ), and microscopic turbulence velocities (v mic ) of the PION components are fixed to values given in Mao et al (2017), which are obtained by fitting the high quality 2002 Chandra grating spectra of NGC 5548. Nonetheless, the ionization parameters (log ξ) can differ for these three epochs, due to the variability of the obscurer, as well as the changes of the intrinsic SED (Cappi et al 2016).…”
Section: The Physical Global Fitmentioning
confidence: 99%
“…Ebrero et al (2016) estimate the distance of the warm absorber components based on variability, with component A and B at least 10 pc away from the central engine and components C to F within 5 pc from the central engine. Nonetheless, based on a spectral analysis using the density sensitive metastable absorption lines, Mao et al (2017) found the warm absorber component B is even closer (<0.23 pc, 3σ upper limit) than the optical NELR, rather than further away. Ebrero et al (2016) constrain the lower limit of the distance of the warm absorber component B based on the non-detection of variability on a timescale of 500 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma models built on extensive and accurate atomic databases are essential to determine plasma parameters that span several orders of magnitudes in the parameter space. For instance, the density of photoionized outflows in the vinicity of black holes can vary from ∼ 10 3−5 cm −3 (C iii, Gabel et al 2005;Arav et al 2015) to 10 6−14 cm −3 (Si ix and Fe xxi, Miller et al 2008;King et al 2012;Mao et al 2017) . Currently, the status of level-resolved electron-impact excitation data of C-like ions is rather poor.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the population of the ground state decreases, and the related spectral features, e.g., lines from ground excitation, become weaker. On the other side, the transitions from the excited states become substantially more important (Mao et al 2017).…”
Section: Appendix A: Density Effectsmentioning
confidence: 99%